Comparison of extraction‐based and elution‐based polymerase chain reaction testing, and automated and rapid antigen testing for the diagnosis of severe acute respiratory syndrome coronavirus 2. Issue 7 (22nd March 2022) - Yoshioka, Nori; Deguchi, Matsuo; Hagiya, Hideharu; Kagita, Masanori; Tsukamoto, Hiroko; Takao, Miyuki; Yoshida, Hisao; Hamaguchi, Shigeto; Maeda, Ikuhiro; Hidaka, Yoh; Tomono, Kazunori
Abstract: We aimed to compare the differences in testing performance of extraction‐based polymerase chain reaction (PCR) assays, elution‐based direct PCR assay, and rapid antigen detection tests for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). We used nasopharyngeal swab samples of patients with coronavirus disease 2019 (COVID‐19). We used the MagNA Pure 24 System (Roche Diagnostics K.K.) or magLEAD 12gC (Precision System Science Co., Ltd.) for RNA extraction, mixed the concentrates with either the LightMix Modular SARS‐CoV PCR mixture (Roche Diagnostics K.K.) or Takara SARS‐CoV‐2 direct PCR detection kit (Takara Bio Inc.), and amplified it using COBAS® z480 (Roche Diagnostics K.K.). For elution‐based PCR, we directly applied clinical samples to the Takara SARS‐CoV‐2 direct PCR detection kit before the same amplification step. Additionally, we performed Espline SARS‐CoV‐2 (Fuji Rebio Co., Ltd.) for rapid diagnostic test (RDT), and used Lumipulse SARS‐CoV‐2 antigen (Fuji Rebio Co., Ltd.) and Elecsys SARS‐CoV‐2 antigen (Roche Diagnostics K.K.) for automated antigen tests (ATs). Extraction‐based and elution‐based PCR tests detected the virus up to 214–216 and 210 times dilution, respectively. ATs remained positive up to 24–26 times dilution, while RDT became negative after 22 dilutions. For 153 positive samples, positivity rates of the extraction‐based PCR assay were 85.6% to 98.0%, while that of the elution‐based PCR assay was 73.2%. Based on the RNA concentration process, extraction‐based PCR assays were superior to elution‐based direct PCR assays for detecting SARS‐CoV‐2.